A Novel Trimetal Phosphide with Amorphous Porous Structure for the Enhanced Electrocatalysis of Oxygen Evolution Reaction. Issue 11 (22nd November 2021) - Wu, Yun; Han, Ping; Li, Bo; Dang, Yuan; Zhou, Yuanzhen
Abstract : Aimed at overcoming the sluggish kinetics of oxygen evolution reation (OER), a novel trimetal phosphide electrocatalyst (CoCuMo-P) with amorphous porous structure was prepared using bimetallic CoCu-ZIF-derived layered double hydroxide (LDH) as the precursor and further pyrolyzing under the PH3 atmosphere. Studies found that the synegistic effect of trimetals and the introduction of P heteroatoms contributed to the optimization of porous morphology, amorphous properties and tuned electronic configuration of CoCuMo-P, which increased the number of exposed active sites and accelerated the mass/electron transfer rate, thereby enhancing the OER electrocatalytic activity of CoCuMo-P. In addition, the in situ formed (oxy)hydroxides and oxides of CoCuMo generated more defective sites and adsorbed OH in the alkaline electrolyte, which further helped to improve the OER catalytic performance of CoCuMo-P. When the applied current density was 10 mA·cm −2, the overpotential obtained on CoCuMo-P lowered to 309 mV and the Tafel slope as low as 76 mV·dec −1 . A 25 h durabilitly was also obtained. The seldomly reported amphorous and porous Cu-containing phosphide enriched the scope of OER electrocatalyst and the underlying reasons for the enhanced OER activity of CoCuMo-P was revealed, which further provided references for the design of novel electrocatalysts.